“Frequency of Meningitis in Children Aged 06 Months to 59 Months Presenting with First Episode of Fits with Fever in Pediatric Emergency Department” - Anum Mustafa, Aiza Mustafa, Razi Ur Rahman, Rozina Iqbal, Oam Parkash, Ariba Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study was aimed to determine the frequency of bacterial meningitis in children aged six months to 5 years presenting with fever and fits for the first time in emergency department. Materials and Methods: This cross sectional study was conducted at the Aga Khan Hospital Karachi and its secondary hospitals including Kharadar, Hyderabdad, Garden, Karimabad sites. Using a non-probability consecutive sampling method the data was collected from 135 children over a period of 12 month from august 2019 to April 2020. In this study, we included the male and female children aged between 6 month to 60 months, Children presenting with fever and first episode of seizure, CSF examination done prior for inclusion in the study. Results: Out of 135 children in the study, 71 (52.30%) children were male, 51(38.46%) were aged between 6months to 24 years, 55(40%) children were in age range 13 to 36 months, 69 (51.50 %) children were completely immunized, 33 (24.60 %) partially immunized. Out of of 135 children ,130 (96%) presents with fits less than 15 minutes duration, whereas 5(4%) children presented with fits more than 15 min duration. Among 50(37%) children who were meningitis positive, 8(6%) were bacterial, 13(10%) were viral and 29 (21%) were partially treated meningitis. Conclusion: Substantial number of children presented with seizures had meningitis. Significant proportion of unimmunized children presenting with seizures had meningitis. , 8(6%) reported with bacterial Meningitis Keywords: Febrile Seizures, Meningitis, Bacterial Meningitis